Health Promoting Properties of Cereal Vinegars - Panagiotis Kandylis; Argyro Bekatorou; Dimitra Dimitrellou; Iris Plioni; Kanella Giannopoulou (Foods, 2021)
Vinegar has been used for its health promoting properties since antiquity. Nowadays, these properties are investigated, scientifically documented, and highlighted. The health benefits of vinegar have been associated with the presence of a variety of bioactive components such as acetic acid and other organic acids, phenolic compounds, amino acids, carotenoids, phytosterols, vitamins, minerals, and alkaloids, etc. These components are known to induce responses in the human body, such as antioxidant, antidiabetic, antimicrobial, antitumor, antiobesity, antihypertensive, and anti-inflammatory effects. The diversity and levels of bioactive components in vinegars depend on the raw material and the production method used. Cereal vinegars, which are more common in the Asia-Pacific region, are usually made from rice, although other cereals, such as millet, sorghum, barley, malt, wheat, corn, rye, oats, bran and chaff, are also used. A variety of bioactive components, such as organic acids, polyphenols, amino acids, vitamins, minerals, alkaloids, melanoidins, butenolides, and specific compounds such as γ-oryzanol, tetramethylpyrazine, γ-aminobutyric acid, etc., have been associated with the health properties of cereal vinegars. In this work, the bioactive components and the related health effects of cereal vinegars are reviewed, and the most recent scientific literature is presented and discussed.